Prevalence and Management of Gastric Leakage After Laparoscopic Sleeve Gastrectomy: A Case Study in Modarres Hospital, Tehran, Iran - Malekpour Alamdari, Nasser; Shafiee, Alireza; Abbasi, Maryam; Besharat, Sara (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Sleeve gastrectomy is an effective procedure for weight loss. However, some serious complications may occur during this operation such as strictures, bleeding, and leak. According to previous studies, the rate of leak was 1.06%. Using endoscopic stents have been hampered by some drawbacks the most important of which is repeated migration. The current study aimed to discuss the prevalence and management of leak after laparoscopic sleeve gastrectomy operated at Modarres Hospital, Tehran, Iran. Methods: This cross-sectional study was conducted on patients with morbid obesity undergone laparoscopic sleeve gastrectomy at Modarres Hospital, Tehran, Iran. In addition to the patients’ demographic data; their leak complications, first symptoms and signs, WBC count, and method of management were extracted and collected from their medical files. Results: A total number of 1263 patients were enrolled in this study. Of them 8(0.63%) patients suffered from leak after the operation. The mean (SD) age of patients with leak was 32.33(6.02) year. The mean (SD) BMI of patients with leak was 45.75(2.07) kg/m2. The mean (SD) of WBC count of the patients with leak was 13680(7272.68). The symptoms of the patients began on different days (3-240 day). Management of the patients was different but most of the patients underwent endoscopic stent. Conclusion: It seems that stent insertion is a useful method for treatment of leak after sleeve gastrectomy, especially in immediate leak.